Predictors of retention and mortality among patients on methadone maintenance therapy - Teoh, Joni Bing Fei; Yee, Anne; Danaee, Mahmoud (Associazione per l'Utilizzo delle Conoscenze Neuroscientifiche a fini Sociali, 2018)
Background: Methadone maintenance therapy (MMT) was started as a pilot project in Malaysia in 2005, and many individuals have benefited from it. Aim: This study aimed to examine the retention rate among patients enrolled in a tertiary hospital MMT programme in Malaysia, as well as factors predicting retention and mortality among these patients. Methods: A total of 164 patients were enrolled in a MMT programme implemented at a tertiary centre in Malaysia between 2005 to 2013. During enrolment, sociodemographic data, blood investigations and urine toxicology were recorded, along with Opiate Treatment Index (OTI) and World Health Organisation Quality of Life (WHOQOL)-BREF scores. Data, including the most recent follow-up date of patients and their daily methadone dose, were obtained retrospectively, in 2015. Retention rate was ascertained on the basis of living patients who stayed in the MMT programme up to 2015. Factors predicting retention rate and mortality were ascertained using Cox’s proportional hazards regression analysis. Results:. The retention rate for MMT at its implementation 10 years ago was 70.1%. Methadone dose ≥ 80 mg/day significantly predicted better retention, while HIV risk-taking behaviour significantly predicted poorer retention in MMT. Mortality was found to be significantly lower among patients of Malay ethnicity and higher among patients who had been found to have HIV and other medical illnesses. Conclusions: MMT retention rate at a tertiary centre in Malaysia was high, but more effort is required to enhance retention among patients with HIV risk-taking behaviour, while also attempting to improve the health of patients with HIV and other medical illnesses.